MODL-27. PRECLINICAL INTERROGATION OF IMMUNOTHERAPY TREATMENT STRATEGIES IN GLIOBLASTOMA (GBM) USING A CLINICALLY RELEVANT DISEASE MODEL. (14th November 2022) - Clerkin, James; Connor, Kate; White, Kieron; Sweeney, Kieron; Shiels, Liam; Van Brussel, Thomas; Arijs, Ingrid; Lambrechts, Diether; Maher, Stephen; Marignol, Laure; Prehn, Jochen; O'Brien, David; et al.
Abstract: Clinically faithful pre-clinical models are essential for screening therapies and studying resistance mechanisms. Historically models have failed to predict response in the clinical setting. Current models seldom incorporate surgical resection, and commonly use young animals whose immune contexture differs from older patients. Here, we have established an orthotopic model, employing the syngeneic, mesenchymal-NFpp10a-cell line, in both young and aged mice. We have characterised the model's response to standard of care resection and temozolomide (TMZ) treatment. We have further studied response to anti-PD1 therapy (adjuvant and neoadjuvant). NFpp10a-Luc2 expressing cells were orthotopically implanted into C57BL/6 mice (aged { > 18months} and young {6-8weeks}) and weekly bioluminescence imaging (BLI) performed to monitor tumour growth. Several therapeutic interventions were assessed to study tumour growth and survival: (1)surgical resection, (2)TMZ, (3)anti-PD1 (4)neoadjuvant anti-PD1. RNAseq, murine microenvironment cell population (mMCP) counter and gene ontology analyses characterised treatment related changed in the TME. We demonstrated survival advantage in aged mice undergoing resection (Resection:33.5 days vs Non-Resection:18 days;p=0.0166). Subsequently, we observed that TMZ and anti-PD1 monotherapy had no impact on NFpp10a-Luc2 growth (TMZ-overall:p=0.9001, and anti-PD1-overall:p = 0.7933) or survival (TMZ-overall:p = 0.3035, anti-PD1-overall:p= 0.6328). Neoadjuvant anti-PD1 treated mice demonstrated no survival advantage compared to IgG control (33-days vs 35-days:p = 0.9429). or BLI signal (p = 0.1703). NFpp10a-Luc2 forms immune-cold TME relative to commonly employed models. mMCP counter analysis demonstrates neoadjuvant anti-PD1 induced influx of CD8+-T cells, B cells, and monocytes into the TME compared to IgG control, and was associated with significantly upregulated CXCR3 chemokine receptor binding pathway on gene ontology analysis (p = 0.0045). Overall, we have, for the first time established and characterised response of the NFpp10a-Luc2-C57BL/6 model to resection, TMZ and anti-PD1 therapies. NFpp10a-Luc2 tumours demonstrate similar therapeutic resistance and TME profile compared to human mesenchymal GBM. The model may therefore be employed in future pre-clinical studies to guide clinical trials in mesenchymal GBM.